2013
DOI: 10.1002/pmic.201200285
|View full text |Cite
|
Sign up to set email alerts
|

Urinary exosomes: A reservoir for biomarker discovery and potential mediators of intrarenal signalling

Abstract: Over the last decade, there has been increasing research interest in urinary exosomes and their relationship with kidney physiology and disease. Protocols for isolating urinary exosomes have been refined and the exosomal proteome has been extensively catalogued and reported to contain proteins from the kidney's glomerulus and all sections of the nephron. In animal and human biomarker discovery studies, this proteome changes to reflect the underlying pathophysiology of certain kidney diseases. In addition to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 39 publications
3
116
0
Order By: Relevance
“…27 In order to validate the exosome purification protocol, we performed western blot analysis on the ultracentrifugation pellets, in comparison with starting urine samples and the ultracentrifugation supernatants (after suitable protein concentration), using antibodies against three commonly used urinary exosomal markers, CD9, TSG101 and Flotillin-1. 28 Results show that urinary exosome-associated protein signals were predominant in the vesicle fraction, and nearly undetectable in total urine or the supernatant (Fig. 1A).…”
Section: Urinary Vesicle Isolation and Characterizationmentioning
confidence: 96%
“…27 In order to validate the exosome purification protocol, we performed western blot analysis on the ultracentrifugation pellets, in comparison with starting urine samples and the ultracentrifugation supernatants (after suitable protein concentration), using antibodies against three commonly used urinary exosomal markers, CD9, TSG101 and Flotillin-1. 28 Results show that urinary exosome-associated protein signals were predominant in the vesicle fraction, and nearly undetectable in total urine or the supernatant (Fig. 1A).…”
Section: Urinary Vesicle Isolation and Characterizationmentioning
confidence: 96%
“…41 More detailed discussion of these challenges can be found in other review papers. 3,44 Currently, there is no single detection technique that can measure the entire size range of EVs (from 30 to 1000 nm). Exosomes are analyzed using a variety of detection techniques.…”
Section: Overview Of Detection Techniques Of Evsmentioning
confidence: 99%
“…3,4 Exosomes are formed by intraluminal budding of endosomal compartments, which create MVBs (Figure 1). 10 Exosomes can, therefore, incorporate cargo, such as soluble proteins, mRNAs, microRNAs (miRNAs), noncoding RNA, mitochondrial DNA, transcription factors, and other cytosolic components and molecules.…”
Section: Characterization Of Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports have demonstrated that urine contains a variety of biomarkers that could indicate diseases. [122][123][124][125][126] Urine contains both urinary and systemic information since urine is in direct contact with urogenital organs and gets filtered from serum via glomerular filtration. Considering genitourinary organs are in direct contact with the body fluid, it is appealing to use urine for prostate cancer diagnoses in a noninvasive manner.…”
Section: From Bodily Fluids To Nanotechnology-based Bioassays Bodily mentioning
confidence: 99%